Catalytic oxidation of lignite to carboxylic acids by molecular oxygen in an aqueous FeCl3 solution. (15th August 2017) - Yang, Fan; Hou, Yucui; Niu, Muge; Wu, Weize; Liu, Zhenyu
Highlights: A new method of production of carboxylic acids (CAs) from lignite was proposed. Lignite was oxidized by O2 with FeCl3 /H2 SO4 catalyst system to yield 51.7 wt% CAs. A synergistic effect of FeCl3 and H2 SO4 significantly promotes the production of CAs. The FeCl3 /H2 SO4 catalyst system shows well reusability. The method is environmentally benign compared with previous alkali-O2 and V-based oxidations. Abstract: Carboxylic acids (CAs) are important chemicals widely used in industrial manufacturing. They can be produced with high yields from O2 oxidation of lignite and the process is regarded promising in the future. However, current methods for the process consume a large amount of mineral alkali and acids, or involve catalysts that are harmful to environment and human beings, and require high temperatures. In this work, we have screened various catalysts and found an iron-based catalyst (FeCl3, Fe2 (SO4 )3 ) to be beneficial for the process. The products include formic acid, acetic acid, oxalic acid, succinic acid and benzene carboxylic acids (BCAs, including 12 types). The effects of FeCl3 concentration, H2 SO4 concentration, reaction temperature, initial O2 pressure and reaction time on lignite conversion and CAs yield are studied. It is found that H2 SO4 can change the catalytic activity of FeCl3 resulting in a synergistic effect for CAs production. In the oxidation process, Fe 3+ is reduced to Fe 2+ by lignite while O2 reoxidizes Fe 2+ to Fe 3+ to form a redox cycle. The catalyst can be reused without significant decline in activity. The method developed in this work requires no alkali and consumes little H2 SO4, and is environmentally benign.